Relación que existe entre los Factores Facilitadores y Obstaculizadores con los conocimientos y habilidades en Investigación que tienen los egresados de la Escuela Académica Profesional de Obstetricia, durante el periodo Agosto a Octubre 2014 - Guevara Arias, William (2014)
This study aimed to determine the relationship between facilitators and hindering factors with the knowledge and research skills that graduates have the Academic Professional School of Midwifery, during the period from August to October 2014 a correlational descriptive research was conducted transverse, with prospective data collection. The sample were 50 graduates who met the inclusion and exclusion criteria. The applied technique for data collection was a structured survey by researchers. To determine the relationship between the variables under study nonparametric test was applied JI square. The results achieved were in the inferential analysis were: There is no statistically significant relationship between the facilitators and hindering factors with the knowledge and research skills are graduates of obstetrics (p> 0.05); reaching the pedagogical dimension as the main facilitator factor (p <0.05). In the descriptive analysis was identified as facilitating factors: motivation, initiative and confidence, interest and creativity of students (81%), use of different materials (78%), satisfaction with the physical and social environment (75%), critical sense and responsible (72%). At the household level is the support of parents in seeking external financing (69%) and active participation (66%). A pedagogical level: instructional support (72%), identification of information resources and technological tools (69%), curriculum (66%) and encouraging the use of the database (56%). Institutionally, it is reported to the creation of research units (81%), training programs, creation of research groups of teachers and students, appropriate context and organization from the office and research institutes (72% respectively). Among the personal hindering factors are located: inadequate (50%) and lack of financial institutions (66%) economic resources. A pedagogical level: the use of management tools for outdated research (75%). Institutional: difficulty in accessing digital libraries (81%), poor internet, weak advice, little knowledge of teachers in the implementation of formative research, weak research competence, diversified approaches and excessive academic load of teachers (72% respectively). 62.5% of graduates were placed in a good level of knowledge tendency to regulate (21.9%) and Malo (15.6%). Regarding skills, shows that 78.1% had developed the ability to research and 21.9% have underdeveloped skills. By the results suggest that the authorities of the Academic Professional School of Midwifery, you must design strategies for achieving continuous improvement chord competent graduates to health and social needs, which contributes to improving health indicators and sustainable development San Martín region, why should handle the upgrade and / or restructuring of the curriculum, a comprehensive curriculum to a competency-based curriculum, to insert subjects and content that help strengthen formative research and knowledge acquisition and research skills of our future graduates.